Stres u koszykarek w różnych grupach wiekowych = Stress female basketball players in different age groups - Wierzbicka, Agnieszka; Napierała, Marek; Pezala, Małgorzata; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Wierzbicka Agnieszka, Napierała Marek, Pezala Małgorzata, Zukow Walery. Stres u koszykarek w różnych grupach wiekowych = Stress female basketball players in different age groups. Journal of Education, Health and Sport. 2016;6(4):319-330. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50224 http://ojs.ukw.edu.pl/index.php/johs/article/view/3476 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016. STRES U KOSZYKAREK W RÓŻNYCH GRUPACH WIEKOWYCH Stress female basketball players in different age groups Agnieszka Wierzbicka, Marek Napierała, Małgorzata Pezala, Walery Zukow Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: koszykarki, stres, mecze w koszykówkę Key words: basketball, stress, matches basketball Streszczenie Celem badań jest poznanie sposobów radzenia sobie ze stresem wśród koszykarek w różnych grupach wiekowych. Badana grupa to koszykarki w wieku od 17 lat do 35 roku życia. Koszykarki na co dzień występują w polskich ligach. Przebadane zostało 125 zawodniczek, z czego 55 (44%) to zawodniczki wieku juniorskiego, natomiast 70 (56%) to seniorki. Wnioski: 1. Koszykarki jako grupa ludzi uprawiających jedną dyscyplinę to zbiór dziewcząt o różnym temperamencie. 2.Większość koszykarek to z natury osoby spokojne. 3. Każda z koszykarek posiada własne sposoby na odreagowanie stresu przedmeczowego, lecz sposoby te powielają się. 4.Grupy seniorskie mają większą odporność psychiczną na mecze rozgrywane w miejscu zamieszkania niż grupa młodsza. 5.W dużym stopniu stres działa motywująco na zawodniczki. 6. Osobami powodującymi stres są trener oraz rodzina i znajomi. 7. Badane koszykarki prawie w ogóle nie korzystają z pomocy psychologów sportowych lub osób z wykształceniem psychologicznym. Abstract The aim of the research is to learn ways of coping with stress among basketball players in various age groups. The study group is basketball at the age of 17 years to 35 years old. The basketball every day occur in Polish leagues. Tested were 125 players, of which 55 (44%) is the junior players age, while 70 (56%) are seniors. Conclusions: 1. The basketball players as a group of people engaged in one discipline is a collection of girls with different temperament. 2.Większość basketball is naturally quiet person. 3. Each of basketball has its own ways to recover from the stress .przedmeczowego, but ways to reproduce themselves. 4.Grupy seniors have greater mental toughness at matches played at home than the younger group. 5. In the largely stress acts as a spur to the players. 6. Persons causing stress are the coach and the family and friends. 7. Tested basketball almost no benefit from the help of sports psychologists or people with psychological education.